2022
DOI: 10.1002/ejlt.202100244
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Sebacic Acid from Castor Oil by New Alternate Route

Abstract: A simple and alternate organic synthetic route for sebacic acid, a high value ten‐carbon aliphatic dicarboxylic acid from castor oil is described in this study. Castor oil methyl esters are purified to obtain methyl ester of ricinoleic acid that is used as the starting material for the preparation of sebacic acid. The hydroxyl group of methyl ricinoleate is oxidized to corresponding 12‐oxo derivative followed by isomerization of the cis 9, 10 olefinic bond to trans 10, 11 isomer. The isomerized compound is sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Since saponification/methylation processes ( Figure S3 ) are helpful for identifying fatty acids [ 62 , 63 ], the major constituents of the oil were detected as methyl or methyl esters derivatives. GC-Trace ultra-system (Thermo Co. USA) was used to analyze each of the studied fixed oils.…”
Section: Methodsmentioning
confidence: 99%
“…Since saponification/methylation processes ( Figure S3 ) are helpful for identifying fatty acids [ 62 , 63 ], the major constituents of the oil were detected as methyl or methyl esters derivatives. GC-Trace ultra-system (Thermo Co. USA) was used to analyze each of the studied fixed oils.…”
Section: Methodsmentioning
confidence: 99%
“…Overcoming the upregulation of P-gp is considered as feasible treatment in drug-resistant epilepsy. Sebacic acid (SA) is a straight-chain, ten-carbon aliphatic dicarboxylic acid normally made from castor oil [97]. In a recently published study, it was reported that SA demonstrated antiseizure activities in MES-and s.c. PTZ-induced seizure models.…”
Section: Sebacic Acidmentioning
confidence: 99%
“…PA1210 is a semi‐biobased polyamide, and one of its raw materials, sebacic acid, is derived from the cleavage of castor oil. [ 34 ] Biobased monomers face challenges concerning the availability of raw materials and production costs. And the cracking by‐products of castor oil, fatty acids, have a variety of uses, including grease, lubricants, and surfactants.…”
Section: Introductionmentioning
confidence: 99%